2018
DOI: 10.1111/jocn.14203
|View full text |Cite
|
Sign up to set email alerts
|

Formalising the precepting process: A concept analysis of preceptorship

Abstract: Continuity throughout an organisation's system streamlines the process of hiring new employees and transitioning nursing students to practice. Organisational policies, dedicated resources and engagement in systematically improving the precepting process are critical. Nurse managers must promote and support formalised preceptorships by providing preceptors and preceptees the time and space needed and fostering a culture that supports preceptorships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 50 publications
(103 reference statements)
0
17
0
Order By: Relevance
“…Moreover, mentors’ motivation is apparently increased by students asking questions and showing clear signs of professional interest, while lack of mentors' encouragement to make students feel part of the nursing team impairs students' experiences in clinical environments (Ford et al, ). Good experiences in mentoring increase nurses' retention (Ward & McComb, ), and positive attitudes, engagement and dedication of healthcare workers enhance learning environments (Tomietto et al, ). In addition, planning clinical practices improves mentors’ attitudes (O'Brien et al, ), and mentors play important roles as role models (ideally displaying high levels of professional patient‐centredness and leading by example) in developing students' professional identity (Felstead & Springett, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, mentors’ motivation is apparently increased by students asking questions and showing clear signs of professional interest, while lack of mentors' encouragement to make students feel part of the nursing team impairs students' experiences in clinical environments (Ford et al, ). Good experiences in mentoring increase nurses' retention (Ward & McComb, ), and positive attitudes, engagement and dedication of healthcare workers enhance learning environments (Tomietto et al, ). In addition, planning clinical practices improves mentors’ attitudes (O'Brien et al, ), and mentors play important roles as role models (ideally displaying high levels of professional patient‐centredness and leading by example) in developing students' professional identity (Felstead & Springett, ).…”
Section: Discussionmentioning
confidence: 99%
“…(Ford et al, 2016). Good experiences in mentoring increase nurses' retention (Ward & McComb, 2018), and positive attitudes, engagement and dedication of healthcare workers enhance learning environments (Tomietto et al, 2016). In addition, planning clinical practices improves mentors' attitudes (O'Brien et al, 2014), and mentors play important roles as role models (ideally displaying high levels of professional patient-centredness and leading by example) in developing students' professional identity (Felstead & Springett, 2016 Jack et al, 2018;Pitkänen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Mentorship projects are symbiotic and reciprocal, providing a win–win situation for both mentor and mentee, and have demonstrated success in improving the quality of care in nursing homes (Feng et al, ; Morrow, ). Numerous studies have shown that mentorship programmes can promote nurse retention, improve nursing staff ability and professionalism and establish a supportive learning environment, resulting in positive resident care outcomes (Burr, Stichler, & Poeltler, ; Schoonbeek & Henderson, ; Schroyer, Zellers, & Abraham, ; Ward & McComb, ). Although there are differences between mentors, preceptors and champions, all serve as helpers who assist mentees or preceptees in improving their knowledge and skills (Agrell‐Kann, ; Greggs‐McQuilkin, ; Wensel, ; Woo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Employee precepts refer to the guidelines and support planned to be provided to employees transferred from other units or services or newly admitted (2) . The qualification and the accompaniment of the new employee demand adequate time and space, so that there is no overlapping of educational and caring functions, thus increasing the workload (18) . This aspect was perceptible to the nurses in the study, and when the number of staff is reduced, the increase in workload may be even greater.…”
Section: Resultsmentioning
confidence: 99%